KERJASAMA INDONESIA - JEPANG MELALUI INDONESIA - JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) DALAM SKEMA MANUFACTURING INDUSTRY DEVELOPMENT CENTER (MIDEC) PADA SEKTOR METAL WORKING PERIODE 2008-2013 - Samira Raihana Khansa, (2021)
This research discusses the cooperation conducted by Indonesia - Japan through IJEPA in the MIDEC scheme in the Metal Working sector. IJEPA itself is a bilateral economic cooperation conducted by Indonesia with Japan to increase trade and investment in Indonesia and Japan in which there are three main pillars, namely, trade liberalization, trade facilitation, and capacity building. In its implementation, there is MIDEC one form in the implementation of IJEPA which is a manufacturing industry development center held with the aim to help improve the competitiveness of the industry and also improve the quality of Indonesian industrial workforce in order to be able to compete and also be able to qualify to enter the Japanese market. Metal Working is one of the sectors involved in the MIDEC scheme because the Metal Working sector itself is one of the important sectors because for metals itself has a connection with other sectors as raw materials. In addition, in other sectors such as the automotive, heavy equipment, and electronics sectors in the process of work there is a process through Metal Working. Therefore, the MIDEC scheme itself is expected to provide good results in its implementation to help improve the quality of Indonesia's industry, especially in the Metal Working sector. This research uses descriptive qualitative research method with the aim to know and analyze the implementation of Capacity Building programs through MIDEC scheme in Metal Working sector. The theory and concept of bilateral economic cooperation, EPA, and Capacity Building are also used as instruments in conducting this research. In that case, Indonesia and Japan have agreed on several activities or programs to be carried out. But, in the realization of cooperation conducted by Indonesia with Japan in the MIDEC scheme in the Metal Working sector has not run optimally because the planned activities carried out are still not fully fulfilled.